Endoscopic ultrasonography in esophageal cancer leads to improved survival rates: Results from a population‐based study. Issue 2 (18th September 2014) - Wani, Sachin; Das, Ananya; Rastogi, Amit; Drahos, Jennifer; Ricker, Winifred; Parsons, Ruth; Bansal, Ajay; Yen, Roy; Hosford, Lindsay; Jankowski, Meghan; Sharma, Prateek; Cook, Michael B.
Abstract : BACKGROUND: The advantages of endoscopic ultrasound (EUS) and computed tomography (CT)–positron emission tomography (PET) with respect to survival for esophageal cancer patients are unclear. This study aimed to assess the effects of EUS, CT‐PET, and their combination on overall survival with respect to cases not receiving these procedures. METHODS: Patients who were ≥66 years old when diagnosed with esophageal cancer were identified in the Surveillance, Epidemiology, and End Results–Medicare linked database. Cases were split into 4 analytic groups: EUS only (n = 318), CT‐PET only (n = 853), EUS+CT‐PET (n = 189), and no EUS or CT‐PET (n = 2439). Survival times were estimated with the Kaplan‐Meier method and were compared with the log‐rank test for each group versus the no EUS or CT‐PET group. Multivariate Cox proportional hazards models were used to compare 1‐, 3‐, and 5‐year survival rates. RESULTS: Kaplan‐Meier analyses showed that EUS, CT‐PET, and EUS+CT‐PET patients had improved survival for all stages (with the exception of stage 0 disease) in comparison with patients undergoing no EUS or CT‐PET. Receipt of EUS increased the likelihood of receiving endoscopic therapies, esophagectomy, and chemoradiation. Multivariate Cox proportional hazards models showed that receipt of EUS was a significant predictor of improved 1‐ (hazard ratio [HR], 0.49; 95% confidence interval [CI], 0.39‐0.59; P < .0001), 3‐ (HR, 0.57; 95% CI, 0.48‐0.66; P < .0001), and 5‐year survival (HR, 0.59; 95% CI, 0.50‐0.68). Similar results were noted when the results were stratified on the basis of histology and for the CT‐PET and EUS+CT‐PET groups. CONCLUSIONS: Receipt of either EUS or CT‐PET alone in esophageal cancer patients was associated with improved 1‐, 3‐, and 5‐year survival. Future studies should identify barriers to the dissemination of these staging modalities. Cancer 2015;121:194–201 . © 2014 American Cancer Society . Abstract : Patients undergoing endoscopic ultrasound (EUS), computed tomography (CT)–positron emission tomography (PET), or EUS and CT‐PET have improved survival at all stages (with the exception of stage 0 disease) in comparison with patients undergoing no EUS or CT‐PET. Receipt of EUS is a significant predictor for improved 1‐, 3‐, and 5‐year survival. Similar results are noted when the results are stratified on the basis of histology and for groups undergoing CT‐PET or EUS plus CT‐PET.